Reinventing The Interpretation of Taqiyya Verse for Strengthening Religious Tolerance - Lilik Ummi Kaltsum; Ahmad Syaifuddin Amin (DINIKA : Academic Journal of Islamic Studies, 2023)
Even though the teaching of taqiyya is explicitly mentioned in the Qur’an, this concept is often negatively connoted as a heretical doctrine of a particular group, especially the Shia. This study aims to explore the interpretation of the Qur’an commentators towards the taqiyya verse (Q.S. Āli Imrān [3]: 28) in order to formulate the concept of taqiyya which can be actualized for the benefit of religious life. By examining the interpretations of some Qur’an commentators from various Islamic sects and implementing the descriptive-analytical method, the study concluded that the interpretation of taqiyya verse is not only limited to life-threatening emergency situations among kāfir ḥarbi, but also considered to be practiced in Muslim relations with non-Muslims or fellow Muslims in ordinary situations. Thus, taqiyya can manifest two main components of tolerance; patience and endurance by hiding beliefs or understandings that have the potential to disrupt the unity and integrity of multicultural society.